Impacts of changing climate on the distribution of migratory birds in China: Habitat change and population centroid shift - Jie Liang (Elsevier, 2021)
Climate changes are related to the changes in the distribution of migratory species, which irreparably harm biodiversity. In this study, we evaluated the habitat change and population centroid shift for 7 orders and 23 different species on the IUCN (International Union for the Conservation of Nature and Natural Resources) Red List of migratory birds from 2014 to 2017 in current to mid-21st (2041–2700) century by Maximum Entropy method (MaxEnt) model. We found that there is significant spatial variability in geographical suitability, with the Yangtze River basin losing 9.74% of suitable habitat and the Pearl River basin losing 13% of habitat. The area of suitable habitat decreases over 3% of total habitat area in China under the RCP 2.6, and decreases about 10% of total habitat area in China under RCP 8.5 scenario, with the population centroid of habitat moving about 50 km to northeast on average. Furthermore, the mean suitability of migratory birds will decrease over 3% in the future, which means environmental variables are changing in directions that are not suitable for birds. Migratory birds will change their habitat and growth cycle in response to the climate change. The direction and distance of the population centroid are different for every species. Most of the individual species in the study will move over 50 km and all the species will move to places with higher suitability. For the whole of China, the constraint for migratory birds is tmin (Minimum temperature). The dominant variable in southeast China is NDVI (Normalized Difference Vegetation Index), while alt (altitude) in the north China. The decline in the suitable habitat area and shift in the population centroid will lead to the changes in the time and distance of the migration process, resulting in more adverse conditions for the survival of migratory birds. Our study proves the adverse role of climate change in species distribution which is a prerequisite for protecting species in the future.